Single-board computers e tecnologias open source na perspectiva educacional - Costa Neto, José Vieira da (2023)
Due to their low cost, great mobility and possibility of transformation, Internet of Things (IoT) devices and Single-Board Computers (SBCs) have conquered more and more space and popularity in academic, residential, and professional environments. There are several SBCs on the market, using Advanced RISC Machine (ARM) processors, which, combined with a GNU/Linux operating system, are ideal for those who do not just want to perform administrative activities. The SBCs also apply to anyone who wants to start developing technologies, tools, and even providing objects of everyday life to be connected to each other, being controlled and accessed through intranet and internet networks. This research presents the importance of SBCs in the educational perspective combined with digital cultural practices, adapting an educational, mobile operating system that includes both educational robotics components and various applications aimed at basic education and Distance Education (EaD). The research has an exploratory character, with the use of a bibliographic survey, with an applied purpose and experimental development, with a quali-quantitative approach. The subjects proposed for this educational operating system are education professionals, teachers from any area of education that requires the use of educational software in the classroom, as well as the locus, all educational environments. As a result, the use of SBCs enabled the development of several tools, such as the educational operating system customized and adapted for Raspberry Pi, TV Box and personal computers, as well as experiments with SBCs in server clusters for small, medium and large applications. , home automation server, retro video games, media centers, among others. It was considered that the use of SBCs and open source technologies are essential for educational practices in different areas of knowledge, contributing as facilitators for a continuous construction of knowledge, however, a greater presence of these resources in classrooms and school spaces is necessary. It is still expected, the development of activities involving educational informatics, with greater mobility, standardization and reduced cost.